PENGARUH KARAKTERISTIK SOSIAL EKONOMI KELUARGA TERHADAP POLA ASUH BELAJAR SISWA SEKOLAH DASAR DAN MENENGAH PERTAMA - Herien Puspitawati (Jurnal Ilmu Keluarga dan Konsumen, 2010)
The main purpose of this research was to know the effect of family socio-economic characteristics towards parenting pattern of studying habits among elementary and secondary high schools. The respondents were parents from elementary and secondary high school. This was a cross sectional study which was performed among 400 parents at District of Indramayu, West Java Province in February-March 2009 who was selected purposively by the school principals. This research used the secondary data from the research investigated by Puspitawati et al. (2009) with title of “Parent Satisfaction Survey of Basic Education Services Provided by Decentralized School System“ that was funded by PRMAP-ADB and Bappenas collaborated with LPPM-IPB. The results showed that most of respondents facilitated their children’s education at home with quite good level of facilities at home. It was shown that parents implemented parenting pattern of studying habits among their children with moderate level of parenting pattern. Based on SEM analysis, it was found that parenting pattern of studying habits performed by parents was influenced directly positive by family social characteristics among elementary students; it was influenced directly and indirectly negative by family social characteristics among secondary high school students; and it was influenced directly positive by family economic characteristics and education facilities at home among all students.